Revision of the South American wasp genus Alophophion Cushman, 1947 (Hymenoptera: Ichneumonidae: Ophioninae) - Alvarado, Mabel (2014)
The species of the strictly Neotropical ophionine wasp genus Alophophion Cushman, 1947 are revised. New descriptions of all previously named species are provided, except Alophophion holosericeus (Taschenberg, 1875) for which the type series is lost and the name is herein considered a nomen dubium. The female of A. flavorufus (Brullé, 1846) is described for the first time. Four informal species groups are proposed based on the morphology of the mandibles, development of the malar space, and general proportions of the head (i.e., development of the face and gena). Whereas the genus previously included only seven named species, it is here expanded to include 49 species (not including the aforementioned nomen dubium), 43 of which are newly discovered and described and thereby increasing the diversity by over eight times. A key to the four species groups and their included taxa is provided. Alophophion is confined to cold and/or dry areas of subequatorial South America, with the exception of A. mancocapaci new species and A. pedroi new species which occur incloud forests around Cuzco, Peru. The genus is newly recorded from Bolivia and Ecuador, and more extensive and accurate distributions are summarized for A. chilensis, A. flavorufus, and A. politus. Alophophion flavorufus is newly recorded from Argentina.Traduce